Native vote: American Indians, the Voting Rights Act, and the right to vote - McCool, Daniel (Cambridge University, 2013)
Publisher description: The right to vote is the foundation of democratic government; all other policies are derived from it. The history of voting rights in America has been characterized by a gradual expansion of the franchise. American Indians are an important part of that story but have faced a prolonged battle to gain the franchise. One of the most important tools wielded by advocates of minority voting rights has been the Voting Rights Act. This book explains the history and expansion of Indian voting rights, with an emphasis on seventy cases based on the Voting Rights Act and/or the Equal Protection Clause. The authors describe the struggle to obtain Indian citizenship and the basic right to vote, then analyze the cases brought under the Voting Rights Act, including three case studies. The final two chapters assess the political impact of these cases and the role of American Indians in contemporary politics